2005
DOI: 10.1007/s10456-005-9005-x
|View full text |Cite
|
Sign up to set email alerts
|

Vascular development in endometriosis

Abstract: Endometriosis, defined as the presence of endometrial tissue outside the uterus, is an estrogen-dependent disease which causes pelvic pain and subfertility in women of reproductive age. The condition has a dramatic impact on the professional, social and marital life of sufferers. Direct and indirect evidence suggests that angiogenesis is required for the development and persistence of endometriosis. In this review the state-of-the-art with regard to our understanding of the role of angiogenesis in the ectopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
121
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(127 citation statements)
references
References 105 publications
4
121
0
2
Order By: Relevance
“…VEGF is a key regulator of angiogenesis (23), which is thought to be involved in the pathogenesis of endometriosis (30). Studies on women with endometriosis compared with healthy controls show differences in both peritoneal fluid composition and the eutopic and ectopic endometrium that relate to angiogenesis regulation (24,26,42).…”
Section: Vegf Involvement In Endo-induced Hyperalgesia?mentioning
confidence: 99%
“…VEGF is a key regulator of angiogenesis (23), which is thought to be involved in the pathogenesis of endometriosis (30). Studies on women with endometriosis compared with healthy controls show differences in both peritoneal fluid composition and the eutopic and ectopic endometrium that relate to angiogenesis regulation (24,26,42).…”
Section: Vegf Involvement In Endo-induced Hyperalgesia?mentioning
confidence: 99%
“…VEGF was first discovered as a specific mitogen of endothelial cell (12), although it is biosynthesized by various cells, including keratinocytes macrophages, platelets, mesangial cells in the kidney and malignant cells (11,(13)(14)(15)(16). As VEGF-induced angiogenesis is an integral step in the pathogenesis of endometriosis, the survival of endometrial implants is primarily dependent on a sufficient supply of blood (17)(18)(19). The early growth of endometrial implants is characterized by a pink-red appearance resulting from its increased vascular density (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…1 Because they initially lack their own blood supply, rapid vascularization is a major requirement for their long-term survival and growth at ectopic sites. 2 Accordingly, endometriosis represents a typical angiogenic disease that is characterized by hypoxia-induced up-regulation of proangiogenic growth factors, formation of new microvascular networks, and adaptive vascular remodeling processes dependent on tissue perfusion. 3 During the past years, several animal and human studies 4,5 have indicated that circulating endothelial progenitor cells (EPCs) from the bone marrow contribute to various postnatal angiogenic processes.…”
mentioning
confidence: 99%